Atanas Dalchev’s ‘Little Tsargrad Mosaic’: A Return to the City of Childhood - Nadezhda Stoyanova (Zeszyty Cyrylo-Metodiańskie)
The paper aims to analyze the seven prose miniatures that the Bulgarian poet Atanas Dalchev (1904–1978) published in 1956 as a collection titled ‘Little Tsargrad Mosaic’. These short texts were among his first literary works which appeared after the establishment of the communist regime in Bulgaria. They became one of the early manifestations of the so-called Thaw in national culture. The miniatures lack public pathos, avoid social issues of their time, and do not contain any vision or notion of the future. In the context of the 1950s, these works demonstrate the main features of Dalchev’s poetics from the 1920s and 1930s, especially interpreting the exterior space through the perspective of the Self. Tsargrad/Istanbul – a place where the poet himself was based twice before 1944 – is the focal theme in the miniatures and is interpreted as a place of return and recognition; a topos where the person, freed from a metaphysical fear, realizes the potential of Being beyond their own singularity. Original title in Bulgarian: „Малка цариградска мозайка” на Атанас Далчев: завръщане в града на детството.